2010
DOI: 10.1186/1472-6874-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing urine samples and cervical swabs for Chlamydia testing in a female population by means of Strand Displacement Assay (SDA)

Abstract: BackgroundThere has been an increasing number of diagnosed cases of Chlamydia trachomatis in many countries, in particular among young people. The present study was based on a growing request to examine urine as a supplementary or primary specimen in screening for Chlamydia trachomatis in women, with the Becton Dickinson ProbeTec (BDPT) Strand Displacement Assay (SDA). Urine samples may be particularly important in screening young people who are asymptomatic.MethodsA total of 603 women aged 15 and older were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
(18 reference statements)
0
19
1
1
Order By: Relevance
“…For detection of C. trachomatis DNA, an accredited (NS‐EN ISO/IEC 17 025) in‐house qPCR was used which amplifies and detect a 112 bp region of the truncated inclusion membrane protein A ( incA ) gene in C. trachomatis The method features a 252 bp Internal Amplification Control (IAC) 27 with primer recognition sites for the C. trachomatis primers and an internal sequence from the pGEM ® ‐luc plasmid (Promega, Maddison, WI, USA), which is recognized by the internal amplification control probe (IAC‐P) 21 …”
Section: Methodsmentioning
confidence: 99%
“…For detection of C. trachomatis DNA, an accredited (NS‐EN ISO/IEC 17 025) in‐house qPCR was used which amplifies and detect a 112 bp region of the truncated inclusion membrane protein A ( incA ) gene in C. trachomatis The method features a 252 bp Internal Amplification Control (IAC) 27 with primer recognition sites for the C. trachomatis primers and an internal sequence from the pGEM ® ‐luc plasmid (Promega, Maddison, WI, USA), which is recognized by the internal amplification control probe (IAC‐P) 21 …”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, samples were taken under precautions to avoid commensal contamination from our instructed physicians committed to good pre-analytical practices [9]; the use of swabs versus smears could not be retrospectively determined.…”
Section: Individuals and Sample Collectionmentioning
confidence: 99%
“…It is now well recognised that studies which evaluate the prevalence of a given infectious condition are based on different analytical procedures, such as epidemiological surveys, questionnaires, laboratory analyses and clinical status [6,8,9]. We were interested to see whether ordering physicians asking selectively for CT and NG or both were right or wrong in their suspicions.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 Previous studies have shown that more women will choose to be screened if it is an easy and noninvasive method, making urine screening the screening test of choice. There are two main ways to screen for chlamydia: cervical swabs or urine tests.…”
Section: Selected Capstone Projectmentioning
confidence: 99%